Generative Learning in a Service-Learning Project and Field-Base Teacher Education Program: Learning to Become Culturally Responsive Teachers. (November 2015) - Assaf, Lori Czop; López, Minda Morren
Research on literacy tutoring such as working in an after-school reading or writing club, situated as a service-learning project, suggests that such work can foster culturally responsive teaching for prospective teachers by increasing additive perspectives toward students from diverse backgrounds and transforming views of diversity. The purpose of this qualitative study was to document the value of participating in a semester long, field-based university course combined with a service-learning program to enhance prospective teachers' generative learning of culturally responsive pedagogy. Building on generative learning theories, we identified the ways prospective teachers became more metacognitive of their past experiences and beliefs, developed caring relationships, and gained confidence about the positive impact they were having on students' literacy learning.